Methodological Proposal to Determine Technology Maturity Levels TRL 4 to TRL 7 for Mobile Applications (2023)
Industries undergoing transformation strategies for improvement can use mobile applications (Apps) to enhance production efficiency, ensure greater coverage, and optimize costs and times. These crucial aspects are imperative to foster confidence among stakeholders. To satisfy this need, maturity assessment models such as the Technology Readiness Levels (TRL) have been developed. This article proposes a methodology to ease the determination of mobile app maturity by mapping them to TRL levels 4 to 7. A review of TRL's application to software products, including mobile applications, indicates that research on it has been conducted but confirmed the absence of a methodology to evaluate their development maturity. With this input in mind, we reviewed different methodologies employed for technological assessment in Apps, selected the most suitable, and designed a set of activities and artifacts that constitute the tool. The methodology was validated through the evaluation of a technological product, and its ability to assess technological maturity at TRL levels 4 to 7 was confirmed. Consequently, we conclude that having tools such as the one presented here is of paramount importance to support research and innovation processes, ensure technological product quality, and comply with the TRL model.